Correlation of MIC with Disc Sensitivity Test of Ampicillin, Amoxycillin and Tetracycline - Haque, AKM Shamsul; Talukder, MA Samad; Rafiquzzaman, Md; Sultana, Sakina; Saha, Pijus; Chakladar, A Hakim (Bangladesh Journal of Medical Science, 2011)
DOI: http://dx.doi.org/10.3329/bjms.v4i3.8230 BJMS 1997; 4(3): 7-11